PEMBELAJARAN PERCAKAPAN BERBAHASA INGGRIS UNTUK SISWA SEKOLAH MELALUI SIARAN RADIO KARYSMA FM PADA PANDEMI COVID-19 - Arini Hidayah; Ika Oktaria Cahyaningrum; Yunita Widiyantari; Widyashanti K Anindhita; Ramadhian Agus Triono S (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
Learning in the Covid-19 pandemic has changed offline learning become online learning. Online learning has several problems for teachers, students, and parents. The covid-19 pandemic in 2020 has had a significant impact in all fields, especially in the education field. Learning English daily conversation through Karysma FM Radio aims to teach students daily conversation and motivate students to deepen their understanding of English subjects outside of school time. The methodology applied in the implementation of community service is observation and the implementing teaching process. The conclusions of learning English daily conversation through Karysma FM Radio are 1) Teaching English daily conversation with students at Karysma FM Radio requires creativity and English language skills; 2) Knowing the psychology of students, it is necessary to invite students to be willing to speak in English daily conversation considering that English subjects are lessons outside of school; 3) The obstacles in teaching English daily conversation with students at Radio Karysma FM are preparation of time and teaching materials